The Effect of Alcoholic Extract of Pomegranate Peel on the level of Erythropoietin and some of the Blood Properties in Albino Male Rats Treated with Erythromycin - Abdul-Zahra , Mushtaq Talib (International Journal of Psychosocial Rehabilitation, 2020)
The study was conducted to evaluate the possible protective effects of alcoholic extract ofthe pomegranate peels against the Erythromycin antibiotic. The study was performed in the animal house of the Department of Biology, College of Education for Girls, University of Kufa, by following (20) Albino male rats from the (Sprague Dawley) strain, which was divided into four groups and each group consists of five males, that weighted between (200-250)g, and the first group was the control group that was orally given physiological solution(0.9%), while the second group was administrated the antibiotic Erythromycin at a concentration of (500) mg / Kg orally, and the third group, it was treated with alcoholic extract of the pomegranate peels with a concentration of (400) mg / kg + Erythromycin with a concentration of (500) mg / kg orallytoo. The last group was orallysubmitted to the alcoholic extract of the pomegranate peels with a concentration of (400) mg / kg, and all the treatments were conducted twice a day, in the morning at (eight in the morning) and the second one at (eight in the evening) every day for fourteen consecutive days. The study included some physiological criteria for the blood, which comprises the numbers of the red blood corpuscles, hemoglobin level, packed cellvolume, platelet count, and total differential count of white blood cells. As for the biochemical study, it included estimating the level of the erythropoietin hormonein the serum. The results of this study showed a significant increase (P< 0.01) in the number of erythrocytes, the level of hemoglobin, and packed cell volume in the group that treated with alcoholic extract of pomegranate peels in compared to the control group and other experimental groups. No notable difference (P> 0.01) was shown in the other criteria that included in the current study, on the contrary, a remarkable decrease (P< 0.01) was observed in red blood corpuscle numbers, hemoglobin level, packed cell volume, platelet count, and percentages (P< 0.05) of lymphocytes, monocytes, acidophils, basophils and erythropoietin hormone level in the group that were treated with Erythromycin, otherwise a significant increase (P 0.01) were obtained between the other study groups. As for the group that was treated with alcoholic extract of the pomegranate peels + Erythromycin, no observable changes(P> 0.01) were shown in comparable to the other groups of experiment. It was concluded from this study that the alcoholic extract of the pomegranate peels has a preventive effect against the toxic impacts that associated with the Erythromycin antibiotic, which may have been caused by its potent anti- oxidant chemical contents.